Preparation, structure characterization and functional properties of pea dregs resistant dextrin - Li, Liangyu; He, Tianfeng; Ling, Yang; Li, Xiaohong; Sui, Chunguang; Cao, Rong-an; Li, Chaoyang (Frontiers in Sustainable Food Systems, 2023)
Background Peas (Pisum sativum L.), the second largest edible bean in the world, have comprehensive and balanced nutrition. In China, peas are mainly used in the processing of starch and related products, during which a large amount of processing by-products—pea dregs—is produced. Because of its large particle size, coarse texture, and difficulty in storage, it is mostly discarded or used as feed, resulting in unnecessary waste. Materials and methods The preparation and simulated moving bed chromatographic purification process conditions of pea-resistant dextrin were optimized using pea production waste-pea residue as raw material, and structural characterization and functional properties of pea residue-resistant dextrin were analyzed. Results The results showed that the optimal preparation process conditions for pea-resistant dextrin were as follows: acid concentration 1.0%, acid addition 7.3%, treatment temperature 178.8°C, and treatment time 92.5 min. Subsequently, the pea-resistant dextrin content of 42.15 ± 0.16% was obtained. The optimal SSMB purification conditions were as follows: feed volume 455 g/h, feed volume 682 g/h, circulation volume 346 mL, outlet concentration 24.8 ± 0.2%, purity 99.35 ± 0.17%, and yield 91.08 ± 0.42%. The structural characterization revealed that pea-resistant dextrin had large and variable particle size and amorphous structure; the chemical bond or functional group differences between pea-resistant dextrin and pea starch were not significant; pea-resistant dextrin was a glucose-based dextran with a monosaccharide composition of 2.6% arabinose, 1.5% xylose, and 95.9% glucose, and its molecular weight was (601.1 ± 8.5) × 103 u. Functional characterization revealed that the RS content of pea-resistant dextrin was 92.35%, which had significantly slow digestive properties as well as hypoglycemic and hypolipidemic effects. Conclusions Using pea dregs to produce pea dregs resistant dextrin has low production cost and significant functional characteristics, which can be widely applied in the food industry.